KARAKTERISASI MAKROSKOPIK DAN MIKROSKOPIK SERTA ISOLASI DNA ISOLAT FUNGI ENDOFIT DAUN EKOR NAGA (Rhaphidophora pinnata L.F Schott) - St Maryam; Siska Nuryanti; Kartini Eka Fakhriyanti Rahbuddin (Fakultas Farmasi UMI, 2022)
Endophyte fungi generally produce secondary metabolites which have biological activities such as anticancer, antiviral, or antibacterial compounds. The endophytic fungi isolate of FM 2 code is one of the endophytic fungi samples of dragon tail leaf (Rhaphidophora pinnata (L.f.) Schott) because it has the best activities. The research aimed to isolate DNA samples of the dragon-tail leaves and to identify the endophytic fungi isolates through macroscopic and microscopic observations. The significance of DNA isolation can be found through electrophoresis, which will show DNA band under the UV light. The results showed that the sample the endophytic fungi isolates on FM 2 code was identified conventionally by observing its morphological characters through macroscopic and microscopic identification compared to literature, showing the similarities to the genus Mucor sp. which will show DNA band under the UV light. The results showed that the sample of endophytic fungi was isolated by a transiluminator UV lamp indicating that the sample was successfully isolated